Pengembangan Media Buku Saku Sebagai Bentuk Pelatihan Microsoft Word di SDN Miagan - Bekti Widyaningsih; Moh. Anshori Aris Widya; Iin Baroroh Ma’arif; Ardisa Audi Khisyara (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
ABSTRACT Microsoft Word training with the development of pocket book media in Miagan Village, Mojoagung District, which is presented in the form of training, is an activity carried out to improve the IT knowledge and skills of students at Miagan Elementary School. The aim of carrying out this Microsoft Word training activity is to provide knowledge about how to operate computers, especially Microsoft Word software, to class V students using media in the form of pocket books. This service method uses an approach to community service activities in the PPM program using the Service Learning (SL) method. The results of Microsoft Word training activities from media development show that students are enthusiastic about learning about how to operate Microsoft Word and they are also able to practice and answer the post tests that have been given.